The methods of scientific research should not be classified either empirical or theoretical - Bermúdez Sarguera, Rogelio; Rodríguez Rebustillo, Marisela (Revista Universidad de Guayaquil, 2016)
This scientific paper focuses the problem of classification of methods of scientific research. Probably covered in theoretical research, not just what they have been awarded scientific knowledge that it is obtained, but also the method by which it is obtained. Is there any chance that supports logical methodological consistency of classification methods in this science are instituted? What reason attends the defense of the idea, that the methodology of scientific research stands through empirical methods, where, regardless of the empirical constitutes the above to the scientific level, the theoretical and the empirical are exclusive natures of knowledge? What arguments invoked in order to demonstrate the falsity of the thesis in which I become identical knowledge and methods according to their scientific nature? Why cling undoubtedly the medieval universal educational thought to absolute canons and the concept of method as a way or path holding? we would not be far from the scientificity that he quintessential definition and it should be given? The basal idea is to defend and to subsume questions formulated above is to be irrevocably dialectical relationship between the method and theory, which necessarily comes firstclassification.
Keywords: classification; method; method of research; scientific knowledge